2017
DOI: 10.3390/mti1020005
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Arts: Current Practices, Potentials, and Implications

Abstract: Abstract:Given that the origin of the "robot" comes from efforts to create a worker to help people, there has been relatively little research on making a robot for non-work purposes. However, some researchers have explored robotic arts since Leonardo da Vinci. Many questions can be posed regarding the potentials of robotic arts: (1) Is there anything we can call machine-creativity? (2) Can robots improvise artworks on the fly? and (3) Can art robots pass the Turing test? To ponder these questions and see the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Artistic performance parameters [24,1] AI system parameters [19,25] Table 1. Areas of extracted features and related works…”
Section: Analyzed Aspectmentioning
confidence: 99%
“…Artistic performance parameters [24,1] AI system parameters [19,25] Table 1. Areas of extracted features and related works…”
Section: Analyzed Aspectmentioning
confidence: 99%
“…Leonardo da Vinci's "Automaton" invented in the 16 th Century can be regarded as the earliest integration of robots and arts [5]. With the electronic and computer revolution, some researchers suggested that this numerical advanced revolution should be matched with art and design.…”
Section: The Collision Between Artificial Intelligence Technology And...mentioning
confidence: 99%
“…Robotic art involves many disciplines [2] such as dance, music, theater, and painting. This work focuses on robotic painting art: technology, that is, machines, robots, computers and sensors, are used for drawing and painting.…”
Section: Introductionmentioning
confidence: 99%